Biosurfactant Production using Candida tropicalis URM 1150 and its Application in the Bioremediation of Coast Environments Impacted by Oil Spills - Maria Catarina de F. Caldas; Renata R. Silva; Hugo M. Meira; Goretti Sonia Silva; Leonie A. Sarubbo; Juliana M. Luna (Frontiers in Bioscience-Elite)
Background: This study aimed to produce, characterize, and apply a biosurfactant as a bioremediation tool for oil-contaminated coastal environments. Methods: The biosurfactant was produced in a medium containing 5.0% corn steep liquor and 1.5% residual frying oil by Candida tropicalis (URM 1150) for 144 hours with 200 rpm agitation. The growth curve and production of the biosurfactant were evaluated. The emulsifying properties and stability of the biosurfactant were tested against pH, temperature, and NaCl variations. Toxicity assays were carried out on seeds, the microcrustacean Artemia salina, and the bivalve Anomalocardia brasiliana. Static and kinetic assays were performed, alongside stone washing to assess the removal capacity. Results: The produced biosurfactant had a surface tension reduction capacity of 70 to 25 mN/m, yielding 7.1 g/L, and a critical micellar concentration (CMC) of 0.4%. During the initial 4-hour cultivation period, the growth curve showed an exponential phase, marked by a constant increase in production. In the final growth stage, biosurfactant production reached its maximum value of 7.1 g/L. After 120 h of cultivation, the maximum biomass output of 9.93 g/L was reached. The biosurfactant was applied in static and kinetic tests with seawater and sand contaminated with oil. The biosurfactant remained stable in the face of the tested variations. The biosurfactant is anionic in nature and showed no toxicity to the microcrustacean Artemia salina, vegetable seeds, or the bivalve Anomalocardia brasiliana, which exhibited 100% survival rates. The biomolecule removed 97% of the contaminated oil on the stone. The biosurfactant proved efficient and biocompatible for the bioremediation of oil derivatives, showing significant removal rates of hydrophobic compounds. Conclusion: These results indicate that the biosurfactant has great potential for application as a remediation agent to clean up oil spills in coastal environments.